(−)-Epicatechin administration protects kidneys against modifications induced by short-term l-NAME treatment in rats. Issue 1 (6th December 2019) - Prince, Paula D.; Fraga, Cesar G.; Galleano, Monica
Abstract : (−)-Epicatechin mitigates NO-mediated impairment of kidney function due to its capacity to modulate NOXs, NOSs, and consequently oxidative stress, and NO bioavailability in the renal cortex of l -NAME treated rats. Abstract : The aim of this work was to evaluate the protective effects of (−)-epicatechin on the kidneys of NO-deprived rats. Male Sprague Dawley rats were divided into three groups: control (C), receiving water and standard diet; l -NAME (L), receiving a solution of N (ω)-nitro-l -arginine methyl ester (l -NAME) (360 mg l −1 in water) as a beverage and standard diet; and l -NAME-(−)-epicatechin (LE), receiving l -NAME solution as a beverage and standard diet supplemented with (−)-epicatechin (4 g kg −1 diet). The L-group showed altered kidney function parameters, evaluated based on plasma urea and creatinine. In parallel, kidney oxidative stress markers, i.e. superoxide anion production, malondialdehyde content, and 3-nitrotyrosine protein adducts, were significantly increased in the L group. In addition, l -NAME treatment induced modifications in kidney NO bioavailability determinants: increased expression of NOX subunits (p47 phox, gp91 phox, NOXO1, and NOX4) and lowered NOS activity. (−)-Epicatechin administration restored kidney function parameters, oxidative stress markers, expression of p47 phox, gp91 phox, and NOX4 and NOS activity to control values. These results indicate that (−)-epicatechin can mitigate NO-mediated impairment of kidney function, in part due to its capacity to modulate NOXs, NOSs, and consequently oxidative stress, and NO bioavailability.